2020
DOI: 10.1002/aoc.6009
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of new palladium (II) complexes with Schiff base type ligands and its impregnated Al2O3 materials: As the catalysts for degradation/reduction of organic dyes

Abstract: The removal of organic dyes used in many sectors such as textile, paper, leather, and packaging from water sources is very important in terms of preventing the spread of industrial pollutants to the environment. Transition metal complexes supported to an inorganic solid material are frequently used for the degradation/reduction of organic dyes causing this pollution. In this study, new Pd (II) complexes with Schiff base ligands were synthesized and structurally characterized by nuclear magnetic resonance (NMR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Catalytic trials were made with 0.1, 0.2, 0.3, 0.4 and 0.5 mmol of NaBH4 to be used as a hydrogen source in catalyst-free environment, and it was observed that the use of NaBH4 above 0.2 mmol did not provide a significant difference in reduction of 4-NP substrate. For this reason, the appropriate amount of NaBH4 for catalytic studies was determined as 0.2 mmol (Selvi et al, 2020). Then, the reduction reactions of 10 mL of 0.01, 0.1 and 1.0 mM aqueous solutions of 4-NP in catalyst-free media in the presence of 0.2 mmol NaBH4 was followed by UV-Vis spectroscopy and the percent conversion values were calculated according to Equation 1 (A0: Initial absorption).…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…Catalytic trials were made with 0.1, 0.2, 0.3, 0.4 and 0.5 mmol of NaBH4 to be used as a hydrogen source in catalyst-free environment, and it was observed that the use of NaBH4 above 0.2 mmol did not provide a significant difference in reduction of 4-NP substrate. For this reason, the appropriate amount of NaBH4 for catalytic studies was determined as 0.2 mmol (Selvi et al, 2020). Then, the reduction reactions of 10 mL of 0.01, 0.1 and 1.0 mM aqueous solutions of 4-NP in catalyst-free media in the presence of 0.2 mmol NaBH4 was followed by UV-Vis spectroscopy and the percent conversion values were calculated according to Equation 1 (A0: Initial absorption).…”
Section: Catalytic Studiesmentioning
confidence: 99%
“…The literature method was utilized for catalytic reactions. 47 Briefly, a test tube containing a solution of 1 mM organic compounds (2-Nitroaniline (2NA), 4-nitroaniline (4NA), Eosin Yellow (EY), Methylene Blue (MB)), 5 mg catalyst (M1-3), and 20 mM NaBH4 was mixed at room temperature. The progress of the catalytic reaction was determined using the UV-Visible spectrophotometer.…”
Section: General Procedures For Catalytic Reactionmentioning
confidence: 99%
“…Supported Pd(II) complexes on solid inorganic materials are commonly used to reduce harmful nitro-aromatics and dyes, such as Eosin yellow, because of their high conversion rates. [44][45][46] Catalyst efficiency increases when Al 2 O 3 is used because of its easy processability and synergistic effects. 47 It is important to develop a relatively simple and inexpensive catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitroarene compounds and toxic dyes are the main pollutants in the wastewater of various industries, including textile and dyeing industries, explosives production, cosmetics production, food industry, pharmaceutical, and paper industries [1,2]. These synthetic organic compounds are highly toxic and one of the most resistant pollutants in the environment [3]. Also, they have adverse effects on the central nervous system, liver, and blood of animals and humans.…”
Section: Introductionmentioning
confidence: 99%